Undergraduate Students’ Perceived Self-Efficacy in Academic Reading - Nahak, Yulius; Mbato, Concilianus L. (Universitas Negeri Semarang, 2022)
Reading academic materials is necessary for acquiring knowledge and new insights to perform well in all academic demands. Nevertheless, many students were still struggling in understanding academic texts due to their high level of complexity and so avoided reading. Thus, self-efficacy as a motivating force and continuous effort in the reading process must be activated. This study aimed to investigate the undergraduate students’ perception of their self-efficacy in handling the academic reading materials. One research question was proposed namely, to what extent do undergraduate students perceive their self-efficacy in reading academic texts? To answer this question, a mixed method was undertaken. The respondents consist of 35 undergraduate students from two private universities in Yogyakarta, Indonesia. The findings indicated that most undergraduate students prefer to read academic texts as a process of constructing meaning. Moreover, to succeed in reading academic text, both external (effective strategies) and internal factors (self-efficacy) were required. One of the implications for teachers and lecturers, namely applying learning procedures that can equip undergraduate students with powerful reading strategies and more importantly stimulate their self-efficacy belief to a stable level which enables them to overcome various difficulties in reading academic texts, such as articles.